The Accountability State : US Federal Inspectors General and the Pursuit of Democratic Integrity - Hilliard, Nadia (Book collections on Project MUSE., 2017)
"The creation of inspector-generals (IGs) in federal agencies began in the 1970's as the size and reach of the federal government grew. IGs are part of the agency but with some independence from the leadership. They are asked to conduct investigations at the request of management or Congress into wrong-doing or the efficiency and effectiveness of government programs. They are seen as a way of making sure that agencies carry out their mandates under law and of enhancing the ability of Congress to conduct oversight. In this book Nadia Hilliard looks at inspectors-general in the Departments of Justice, State, and Homeland Security in order to see if IGs enhance democratic control over these bureaucracies. She argues that the effectiveness of the IG as a means of democratic accountability varies depending on the degree of independence of the IG, the resources available, the stability of the leadership, the ability to develop an appropriate focus of work, and the ability to develop on-going programs of monitoring in the agency. Their contribution lies mainly in their ability to create a narrative about a government program and publicize that story"--